Cultural differences in the development of processing speed. Issue 3 (19th March 2013) - Kail, Robert V.; McBride‐Chang, Catherine; Ferrer, Emilio; Cho, Jeung‐Ryeul; Shu, Hua
Abstract The aim of the present work was to examine cultural differences in the development of speed of information processing. Four samples of US children (N = 509) and four samples of East Asian children (N = 661) completed psychometric measures of processing speed on two occasions. Analyses of the longitudinal data indicated that, although processing speed was comparable among US and East Asian children at the youngest age (~4.5 years), it developed more rapidly in some but not all of the East Asian samples. Results are discussed in terms of factors that may promote more rapid development of processing speed in some East Asian cultures.